Rethinking Consciousness: Extraordinary Challenges for Contemporary Science edited by John H. Buchanan and Christopher M. Aanstoos - Kelly, Edward F. (Journal of Scientific Exploration, 2022)
This slender volume is the twentieth member of a series entitled “Toward Ecological Civilization,” organized under the leadership of distinguished process philosopher and process theologian John B. Cobb, Jr. It grew directly from the 10th Whitehead International Conference, held in Claremont, California, in June 2015, and more particularly from a single conference track (out of the more than 80 making up the program) devoted specifically to various kinds of “extraordinary experiences” (especially, parapsychological and transpersonal experiences) that directly challenge the materialist/physicalist worldview which arose in the 17th century and still dominates the contemporary scientific, educational, and cultural mainstream. The central premises of the series as a whole, the 2015 conference, and the present volume are that postmodern civilization faces life-threatening crises rooted in that impoverished physicalist worldview, that we desperately need a more commodious, life-affirming, and ecologically sound alternative to it, and that Whitehead’s metaphysical vision can help take us in the needed direction. Like Stanley Krippner in the book’s brief Foreword, I am strongly sympathetic to these views.